Antifungal Susceptibility of Candida Species Isolated from Horticulturists with Onychomycosis in Piauí, Brazil - Mitra MOBIN; Maria Walderez SZESZS; Juliana Possatto TAKAHASHI; Marilena MARTINS; Daise Damaris Carnietto de HIPPÓLITO; Jhonatas Cley Santos PORTO; João Batista TELES; Sidney Gonçalo de LIMA; Marcia de Souza Carvalho MELHEM (Tehran University of Medical Sciences, 2018)
Background: We aimed to assess susceptibility pattern of Candida species isolated from horticulturists with onychomycosis to four antifungal drugs and to compare the effectiveness of conventional identification methods with matrix-assisted laser desorption/ionization mass spectrometry (MALDI-TOF MS). Methods: This study was conducted in a community garden located in Teresina, State of Piauí, Brazil, in the year 2014. The samples were identified through phenotypic methods and per MALDI-TOF MS, being used PCR as definitive identification test. The susceptibility pattern to four antifungal drugs was determined according to Clinical and Laboratory Standards Institute (CLSI). Results: Fourteen clinical isolates from seven different species were identified by the phenotypic method and by MALDI-TOF MS, with an observed concordance of 71.4% between the two methods. C. albicans (28.6%), C. parapsilosis (21.4%), C. guilliermondii and C. metapsilosis (both with 14.3%) were the most frequent species. With the exception of C. krusei, all species were sensitive to the tested antifungal. Conclusion: This is the first study of antifungal susceptibility of Candida in Piauí, Brazil. With the exception of C. krusei, no species showed resistance to the antifungal drugs used. This study suggests constants updates from the public databases used in MALDI-TOF MS to provide a rapid and accurate mycological diagnosis.